MULTIPLE MICRONUTRIENT (ZINC, MAGNESIUM) THERAPY TO SEVERE MALNOURISHED CHILDREN: EFFECT ON GROWTH CATCH UP AND CLINICAL RECOVERY - Ahsan, Touhida; Rahman, Mustafizur; Ramatullah, Md.; Ahsan, Monira; Islam Khan, Md. Nazrul; Islam, Sheikh Nazrul (European Scientific Journal, ESJ, 2013)
Objective: to supplement zinc and magnesium to severe malnourished children aiming to improve catch up growth and clinical recovery. Design: It was a case control study conducted among one hundred severely malnourished children who were purposively enrolled from the nutritional unit of Dhaka Shishu Hospital, Dhaka, Bangladesh. The children were distributed in four groups each comprising twenty-five children having uniform morbidity. Along with the recovering diet and nutrient supplements, the interventional three groups received single zinc, single magnesium and combination of zinc and magnesium therapy. The control group received only the recovery diet and supplement. Increment of growth catch up and hospital stay time was measured and recoded. Setting: Nutritional unit of Dhaka Shishu Hospital, Dhaka, Bangladesh. Subjects: one hundred severe malnourished children. Results: It was resulted in that single zinc or magnesium and combination of zinc-magnesium therapy significantly (p<0.05) improved the growth catch-up and clinical recovery of the malnourished children. Conclusions: Multiple Zn and Mg therapy was found to be more effective than the single Zn or Mg therapy in improving the growth catch-up and clinical recovery of the malnourished children.